2017
DOI: 10.4085/1062-6050-52.2.16
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Skin Infections in Men's Wrestling: Analysis of 2009–2010 Through 2013–2014 National Collegiate Athletic Association Surveillance Data

Abstract: academic years. Design: Descriptive epidemiology study. Setting: Aggregate skin infection and exposure data collected by the NCAA Injury Surveillance Program.Patients or Other Participants: Collegiate men's wrestling student-athletes.Main Outcome Measure(s): All viral, bacterial, or fungal skin infections reported by athletic trainers at 17 NCAA programs were analyzed, providing 35 team-seasons of data. Skin infection rates per 10 000 athlete-exposures (AEs), rate ratios, skin infection proportions, and skin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…In preparing content and areas of emphasis for class and assessment, surveillance tracking for dermatologic infections in NCAA wrestling 4 has been considered. For example, because viral infections are 1.7 times as common as bacterial infections and 2 times more common than fungal infections, 4 content focuses more on viral and bacterial conditions than on fungal conditions, although common conditions in all categories are presented. In addition, because dermatological conditions are not isolated to skin infections, more generalized conditions such as sunburn, contact dermatitis, and perichondritis (eg, cauliflower ear) are included in this module.…”
Section: Content Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In preparing content and areas of emphasis for class and assessment, surveillance tracking for dermatologic infections in NCAA wrestling 4 has been considered. For example, because viral infections are 1.7 times as common as bacterial infections and 2 times more common than fungal infections, 4 content focuses more on viral and bacterial conditions than on fungal conditions, although common conditions in all categories are presented. In addition, because dermatological conditions are not isolated to skin infections, more generalized conditions such as sunburn, contact dermatitis, and perichondritis (eg, cauliflower ear) are included in this module.…”
Section: Content Developmentmentioning
confidence: 99%
“…3 In regard to these conditions, surveillance tracking in wrestling in particular indicates that about 21% of dermatologic infections are recognized during practice and result in an average of 24 hours of missed participation time. 4 Moreover, persons who have suspected dermatologic infections are instructed to be medically evaluated by a physician and/or athletic trainer before participation. 5,6 Given that so many of these infections are identified during practice, the athletic trainer is well suited to serve as the first point of evaluation for dermatological conditions and the continued point of contact in preparation for return to activity.…”
Section: Introductionmentioning
confidence: 99%
“…To better prevent and control infectious disease outbreaks, routine prevention and control measures, new technologies for symptom surveillance, environmental sampling, and virus testing are used in major sports events. Routine prevention and control measures include reminding participants to pay attention to personal hygiene, and strengthening publicity, education, and cooperation between health institutions [ 14 , 15 ]. For infectious disease surveillance and management, before the 1990s, major sports events mainly used traditional methods relying on routine manual filing of reportable diseases by clinicians [ 16 - 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the epidemiology of skin infections in sport, including HZ, is rare in general, and that in pediatric populations still rarer (9). A 2017 study looking at NCAA surveillance data in the high-risk sport of collegiate wrestling found an overall skin infection rate of 14.23/10,000 athletic exposures (AEs), with viral infections occurring more frequently than bacterial infections (9). Herpes simplex skin infections in this cohort were commonly seen (rate 6.35/10,000 AEs), whereas herpes zoster was uncommon, with a reported incidence of only 0.25/10,000 AEs (9).…”
Section: Introductionmentioning
confidence: 99%
“…A 2019 study reported an incidence of 74 per 100,000 person years for unvaccinated children and 38 per 100,000 person years for children who are vaccinated (3). Knowledge of the epidemiology of skin infections in sport, including HZ, is rare in general, and that in pediatric populations still rarer (9). A 2017 study looking at NCAA surveillance data in the high-risk sport of collegiate wrestling found an overall skin infection rate of 14.23/10,000 athletic exposures (AEs), with viral infections occurring more frequently than bacterial infections (9).…”
Section: Introductionmentioning
confidence: 99%